A Review of Experimental Trawling from Small and Medium Sized Mechanised Vessels off Kakinada - Satyanarayana, A. V. V.; Narayanappa, G. (Fishery Technology, 1972)
Mechanization of fishing craft in this part of India started with the introduction of powered gill netters during the late fifties. Combined with the use of synthetic twinesthe performance of these gill netters was quite encouraging. It is in this background that the C. I. F. T. Sub-Station at Kakinada took up work on developing bottom trawling gear for small and medium sized mechanized boats. The results of the work during the years 1963-'70 are presented in this paper. The most suitable otter trawl for small boats was found to be 10.9 to 15m two seam trawl with 100 cm. x 50 cm x 35 kgs horizontally curved otter boards together with long single sweep line.